Lipid profile changes in patients undergoing bariatric surgery: A comparative study between sleeve gastrectomy and mini-gastric bypass. (February 2015) - Milone, Marco; Lupoli, Roberta; Maietta, Paola; Di Minno, Alessandro; Bianco, Paolo; Ambrosino, Pasquale; Coretti, Guido; Milone, Francesco; Di Minno, Matteo Nicola Dario; Musella, Mario
Abstract: Objective: To prospectively evaluate the effect of different types of bariatric surgery on lipid profile. Methods: Total cholesterol (TC), High-Density-Lipoprotein cholesterol (HDLc), Low-Density-Lipoprotein cholesterol (LDLc) and triglycerides (TG) levels were evaluated before surgery and at 3 different post-operative time-points (3, 6 and 12 months) in consecutive obese subjects undergoing mini-gastric bypass (MGB) or sleeve gastrectomy (SG). Results: At baseline, 74 MGB and 86 SG subjects were comparable for lipid profile and prevalence of hypercholesterolemia/hypertriglyceridemia. During the post-operative follow-up, both MGB and SG subjects showed significant changes in lipid profile. However, at 3 months, MGB patients showed higher changes in TC (β = 0.179, p = 0.022) and TG (β = 0.265, p = 0.001) than those undergoing SG. At 6-month post-operative follow-up, these differences were confirmed only for TC. After a 12-month follow-up, MGB and SG were entirely comparable for changes in lipid profile with the exception of HDLc, whose changes were higher in SG group (β = 0.130, p = 0.039). Overall, the probability to normalize lipid profile during the 12-month follow-up was similar in MGB and in SG patients (OR:1.24, 95%CI:0.41–3.76, p = 0.689). Conclusion: Despites some differences at 3–6 post-operative months, during a 12-month follow-up, SG and MGB showed a similar efficacy in the improvement of lipid profile of obese patients. Highlights: This is the first study, in our best knowledge, comparing the effects of Mini-Gastric Bypass and Sleeve Gastrectomy on the lipid profile. The overall effect on lipid profile improvement was similar between Sleeve and Bypass. By a cardioprotective point of view, sleeve could be preferred in patients with dyslipidemia, a higher increase of HDLc being documented.